UNIX® User's Handbook, Second Edition - Poniatowski, Marty (Hewlett-Packard professional books., 2001)
The in-depth UNIX guide for every end-user: completely updated and full of examples! For every key UNIX platform: practical examples, real depth! Covers all basic UNIX commands, plus sed , grep , awk , vi , and more Complete shell programming coverage-plus NEW programming section covering C/C++, Java(tm), and Internet development KornShell, Bash, C Shell, and Shell Programming Windows interoperability, in depth: Samba, NFS, Windows 2000 Services for UNIX, and much more UNIX end-users desperately need an up-to-date reference guide with real depth: one that teaches UNIX commands and doesn't just list them! In UNIX User's Handbook, Second Edition , best-selling UNIX author Marty Poniatowski covers every topic UNIX users need to master-with exceptional clarity and practical, real-world examples. Part I brings together thorough coverage of virtually every key aspect of day-to-day UNIX operation and end-user administration. Part II presents an in-depth programming reference. Part III covers every leading option for Windows interoperability. You'll find fast, easy answers for all this and more: Getting started: login, mail, Internet access, and key UNIX file management commands All basic UNIX commands and a complete UNIX file system overview (cd, cp, file, ls, mv, pwd, rm, rmdir, cut, paste, split, sort, diff, and more) Key UNIX tools-including in-depth coverage of find, vi, find, grep, sed, and awk Shells and shell programming: Bash, Korn, and C Full programming section-including a NEW user-centered introduction to C/C++ and Java End-user administration: processes, startup, shutdown, users/groups, backup, software management, printing, and more Networking and Internet protocols UNIX/Windows interoperability: Samba, X Window, NFS, Posix, Windows 2000 Services for UNIX, and other alternatives Performance and monitoring This new edition has been updated throughout and redesigned for even faster, easier access to information. Whatever your experience, whatever UNIX version you use, you won't find a more useful reference!